2007
DOI: 10.1038/sj.eye.6702965
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathological analysis of vitreous in intraocular lymphoma

Abstract: Objective To describe the cytopathological method used in the analysis of vitreous samples in the diagnosis of primary intraocular lymphoma (PIOL). Participants Seven patients with refractory posterior uveitis referred to a regional ocular inflammatory service were diagnosed as having PIOL between 1999 and 2006. Methods Clinical features of the uveitis and cytopathological preparation of the samples were described. All patients underwent vitrectomy and samples were placed in formal saline or prepared fresh. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
(11 reference statements)
1
24
0
3
Order By: Relevance
“…[4][5][6][7]9,10,20,21,26,[30][31][32][33][34][35] These include: (1) vitreous 'filtration'; (2) a celloidin bag technique; (3) cytospin and (4) cell block preparation. We are most familiar with the latter two methods, whereby the vitreous is spun at 500 r.p.m.…”
Section: Sample Handling and Processingmentioning
confidence: 99%
“…[4][5][6][7]9,10,20,21,26,[30][31][32][33][34][35] These include: (1) vitreous 'filtration'; (2) a celloidin bag technique; (3) cytospin and (4) cell block preparation. We are most familiar with the latter two methods, whereby the vitreous is spun at 500 r.p.m.…”
Section: Sample Handling and Processingmentioning
confidence: 99%
“…Nevertheless, of equal importance is the exclusion of infection or masquerade, and AC sampling is increasingly being used for this purpose, the most classic example of which is the advances achieved in the diagnosis of primary intraocular lymphoma by measurement of aqueous IL-10 and/or IL-10: IL-6 ratios, and by vitreous biopsy, utilising modern immunohistochemistry, flow cytometry, and PCR to facilitate diagnosis. 103 The utility of sampling AC or vitreous is also to discriminate infectious causes from autoimmune/inflammatory disease. By PCR or by Goldmann-Witmer co-efficient of specific antibody production against microbes/viruses we are now able to discern more precisely possible infectious causes, which as a result will direct treatment appropriately.…”
mentioning
confidence: 99%
“…The preparation of vitreous samples for cyto-pathological analysis has also changed over time to improve yields from this limited specimen. Intzedy et al reported that samples placed in saline or prepared fresh followed by paraffin embedding were able to yield a positive diagnosis [48].…”
Section: Diagnosismentioning
confidence: 99%